1979
DOI: 10.1159/000220889
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotika zur Prophylaxe der Begleitthrombosen bei infraklavikulären Vena-Cava-Kathetern

Abstract: Um die Suppressibilität von Thrombosen im Gefolge von Vena-Cava-Kathetern nach 6- bis 8tägiger Verweildauer mittels Phlebographie zu prüfen, erhielten je 25 Patienten nach entsprechenden präoperativen Initialdosen Low-dose-Heparin, Dextran 70 oder Azetylsalizylsäure. Als Kontrolle dienten 25 Patienten ohne antithrombotische Medikation. Bei letzterer Untersuchungsgruppe konnten bei etwa einem Drittel der Fälle Thrombosen objektiviert werden. Mit Azetylsalizylsäure verringerte sich die Thromboseanfälligkeit sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This study provides no information on the value of prophylactic treatment (dextran 70, LDH) in reducing CVC-induced thrombosis. In patients undergoing operation, Fassolt and Braun [6] found no difference in major thrombosis developing around CVC between patients receiving low-dose heparin (5,000 IU twice daily) and a control group without heparin. In a similar comparison with dextran 70, Brfindli and Fassolt [7] found a 16% incidence of CVC-induced thrombosis in the treated group and 36% in the controls.…”
Section: Discussionmentioning
confidence: 95%
“…This study provides no information on the value of prophylactic treatment (dextran 70, LDH) in reducing CVC-induced thrombosis. In patients undergoing operation, Fassolt and Braun [6] found no difference in major thrombosis developing around CVC between patients receiving low-dose heparin (5,000 IU twice daily) and a control group without heparin. In a similar comparison with dextran 70, Brfindli and Fassolt [7] found a 16% incidence of CVC-induced thrombosis in the treated group and 36% in the controls.…”
Section: Discussionmentioning
confidence: 95%
“…The available information supports this practice. [169][170][171][172][173][174][175][176][177] Umbilical arterial lines: The current practice of using low dose UFH infusions was evaluated in a metaanalysis in newborns. 169 Patency, which is likely linked to the presence of local TEs, was prolonged by the use of low doses of UFH.…”
Section: Guidelines For Antithrombotic Agentsmentioning
confidence: 99%
“…A Medline search identified ten clinical trials assessing heparin in CVLs. [39][40][41][42][43][44][45][46][47][48] Four trials showed that heparin is associated with a strong trend for reducing CVL-related fibrin sheath formation. [45][46][47][48] Six trials assessed the impact of heparin on partial or total occlusion of vascular flow and that heparin decreased CVL-related thrombosis.…”
Section: Central Venous Linesmentioning
confidence: 99%
“…[45][46][47][48] Six trials assessed the impact of heparin on partial or total occlusion of vascular flow and that heparin decreased CVL-related thrombosis. [41][42][43][44]46,48 Together these data suggest that heparin prophylaxis should be strongly considered for the preservation of CVL patency and perhaps reduce the risk of associated TEs.…”
Section: Central Venous Linesmentioning
confidence: 99%